DETERMINATION OF ASH CONTENT IN COAL BY X-RAY FLUORESCENCE ANALYSIS - Baimolda, D; Cechak, T.; Shyngysova , Sh. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses the advantages of X-ray fluorescence analysis (XRF) techniques for the determination of ash in coal. The quality of coal depends on the amount of ash contained in it. On the other hand, ash causes irreversible environmental damage when using coal as a source of energy. Since coal is considered as the most important source of energy, coal quality is directly related to ash, which correlates with its non-combustible minerals and elements. Some elements such as S (sulfur), Ti (titanium), Ca (calcium), Fe (iron) after burning coal can have an adverse impact on the environment. Thus, we have demonstrated in this study how we can determine the ash content consisting of noncombustible minerals in the composition of coal and, thus, assess the quality of coal using X-ray fluorescence research. It also describes how we can determine coal ash samples using the XRF analyzer 123-1 in online, which is one of the most optimal methods in nuclear physics.